Sex Differences in the Association between Level of Childhood Interleukin-6 and Insulin Resistance in Adolescence. (5th January 2012) - Bugge, Anna; El-Naaman, Bianca; G. McMurray, Robert; Froberg, Karsten; Nielsen, Claus Henrik; Müller, Klaus; Andersen, Lars Bo
Abstract : The purpose of this study was to determine whether levels of interleukin-6 (IL-6) in childhood are related to insulin resistance in adolescence. Further, to explore how fatness and cardiorespiratory fitness (VO 2peak ) moderate this relationship. Methods . 292 nine-year-old children (n = 292 ) were followed for 4 years. Anthropometrics and VO 2peak were measured. Fasting blood samples were analyzed for IL-6, insulin, and glucose. Homeostasis model assessment (HOMA-IR) was used as a measure of insulin resistance. Results . For girls but not boys, levels of IL-6 at age 9 yrs correlated with HOMA-IR at age 13 yrs: r = 0.223, P = 0.008 . Girls with IL-6 levels within the highest quartile at age 9 yrs had an odds ratio of 3.68 (CI = 1.58–8.57) being in the highest quartile of HOMA-IR four years later. Conclusion . In this cohort, IL-6 levels in childhood were related to insulin resistance in adolescence, but only for girls.